Pengaruh Penyimpanan Cloud Terhadap Pelanggaran Keamanan - Nur Aida; Rayyan Firdaus (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research examines the impact of the use of cloud storage by companies on various types of security breaches, both in the short and long term. Adoption of cloud storage is associated with an increase in external breaches and unintentional internal errors in the short term. However, over time, the positive relationship between use of Cloud storage and external infringement becomes less significant in the long term. Research findings show that use of cloud Storage can reduce the risk of unexpected internal error in the longer term, but does not have a significant relationship with harmful internal breach. This research confirms the importance of companies allocating resources wisely to manage security risks in using cloud storage for both short- and long-term purposes. The researchers contributed to an understanding of the security of cloud storage by applying the theory of attention, which highlighted the importance of paying attention to temporal aspects in the management of enterprise IT security through various attention mechanisms.